2015
DOI: 10.1177/0194599815622409
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Yield as a Predictor of Survival in Pathologically Node Negative Oral Cavity Carcinoma

Abstract: These data suggest that patients with oral SCC undergoing elective neck dissection may experience an overall survival benefit associated with greater lymph node yield. Mechanisms behind the demonstrated survival advantage are unknown. Larger nodal dissections may remove a greater burden of microscopic metastatic disease, diminishing the likelihood of recurrence. Lymph node yield may serve as an objective measure of the adequacy of lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 35 publications
4
78
0
1
Order By: Relevance
“…Cervical lymphadenectomy remains the gold standard for nodal staging in cN0 patients with high‐risk head and neck SCCA . The accuracy of surgical staging in the cN0 neck depends on the number of lymph nodes removed and the sensitivity of the pathological methods for detecting occult metastatic disease …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cervical lymphadenectomy remains the gold standard for nodal staging in cN0 patients with high‐risk head and neck SCCA . The accuracy of surgical staging in the cN0 neck depends on the number of lymph nodes removed and the sensitivity of the pathological methods for detecting occult metastatic disease …”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin immunohistochemical analysis can detect a single epithelial cancer cell in a lymph node; several studies have demonstrated a wide detection rate of micrometastatic disease using this technique . Prognostic implications of micrometastatic disease are not fully understood, but recent studies suggest the increased detection of micrometastatic disease with higher LNY may account for improved overall survival …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The authors queried the SEER database over an 11-year period from 1988 to 2009 and identified a total of 4341 patients with oral cavity SCC who were determined to be pN0 after elective lymph node dissection. They then studied the number of lymph nodes removed and its impact on overall survival.…”
mentioning
confidence: 99%